Mécaniques de la catharsis héroïque : la création du héros grec - Hélène Bernier-Farella (Otium, 2017)
Although Greek heroic’s cultic personalities are usually presented as an irreducibly heterogeneous group, we propose here to stress, in the mythic aitia, some common grounds that are able to define them as a coherent cultic group. General mechanisms of hero-making seem to lie in their very particular death, which implies critical, proven or potential religious pollution, which befall on the all community.